PCR and ELISA vis-à-vis Microscopy for Detection of Bovine Anaplasmosis: A Study on Associated Risk of an Upcoming Problem in North India - Amrita Sharma; L. D. Singla; Paramjit Kaur; M. S. Bal (The Scientific World Journal)
This investigation demonstrates the status of bovine anaplasmosis caused by A. marginale in bovines from Submountain and Undulating Zone of Punjab. Out of 184 suspected animals, 25 (19.51%), 47 (31.71%), and 78 (68.75%) were positive by microscopy, indirect ELISA, and PCR assay, respectively. The microscopy showed 29% sensitivity and 99% specificity, while ELISA showed 32% sensitivity and 79% specificity in concordance with PCR assay. Five false negative samples by msp1β PCR were reconfirmed for Anaplasma spp. targeting 16S rRNA gene. The sequence analysis showed the presence for A. marginale specific restriction site, indicating variation in the local strains of the organism resulting in no amplification with msp1β gene primers. Of 82 samples positive by PCR, 57 were negative by ELISA indicating lower efficacy of ELISA to detect early anaplasmosis. The assessment of risk factor with results of PCR technique indicated that cattle (Odds ratio = 2.884), particularly those of age > 1 years (Odds ratio = 2.204) of district Pathankot (Odds ratio = 3.182) of Submountain Zone (Odds ratio = 2.086), were at high risk of anaplasmosis. All three districts of Submountain Zone are at higher risk indicating the impact of biotic and abiotic factors on the incidence of disease.